Estado e reestruturação urbana em Sergipe (2000 - 2018): uma análise sobre os principais programas de habitação de interesse social - Antonio Carlos Campos; Flávio Henrique Matos Santos (Confins)
The study aims to discuss the State's role in the process of urban space production in Sergipe and, mainly in Aracaju, through the provision of social housing linked to programs: Moradia Cidadã, Arrendamento Residencial, Programa de Aceleração do Crescimento e, Minha Casa, Minha Vida. Also, its structuring and contradictory spatial knocking. The timeframe extends from the 2000s to the present days. The object is part of a broader study that analyze the agents and the urban restructuring of Sergipe state cities. The methodological choice was qualitative and quantitative research with systematic procedures involving secondary data search and thematic mapping. They were used to analyze the production of fractions of these spaces through the different housing policies addressed to the « less favored people ».